Citizenship - J M Barbalet; BARBALET (J M) (Milton Keynes Open University Press, 1988)
Relies heavily on the theories and criticism of T.H. Marshall expounded in Citizenship and social class (1950) and limits empirical discussion to Britain. Cloth edition $29.50 (not seen). Annotation copyrighted by Book News, Inc., Portland, OR
Keywords: Citizenship Rights; Social Classes; Class Inequality; Political and Social Integration; Social Movement in Citizenship